The Effect of Pop-Up Digital Book Media on Fourth-Grade Students’ Vocabulary Comprehension in English Learning - Syahdila Intan Andira; Latri Aras; Abdul Malik Ramli (International Journal of Elementary School Teacher, 2026)
This study investigated the effect of Pop-Up Digital Book media on fourth-grade students’ vocabulary comprehension in English learning at SDN Kalukuang 2 Makassar. The study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. The participants consisted of 40 students divided into an experimental group (n = 20) and a control group (n = 20). Data were collected through classroom observations, vocabulary comprehension tests, and documentation. The data were analyzed using descriptive statistics and an Independent Samples t-test. The findings revealed that the implementation of Pop-Up Digital Book media was carried out effectively, as indicated by an increase in observation scores from 70% to 90% during the treatment sessions. Students in the experimental group demonstrated substantially higher vocabulary comprehension scores than those in the control group. The mean score increased from 49.50 in the pretest to 74.00 in the posttest, whereas the control group showed only a slight improvement. Hypothesis testing indicated a statistically significant difference between the two groups (p < 0.05), confirming that the use of Pop-Up Digital Book media had a significant positive effect on students’ vocabulary comprehension. These findings suggest that interactive digital learning media can enhance vocabulary acquisition, increase student engagement, and support more effective English language learning at the elementary school level.